Efficacy of acupuncture for stroke-associated pneumonia: a systematic review and meta-analysis - Kaihan Su; Kaihan Su; Xiaoyu Wang; Xiaoyu Wang; ShiYin Zhang; ShiYin Zhang; Jiantong Wu; Jiantong Wu; Yuqi Chen; Lianjun Yin; Haunan Li; Haunan Li; et al. (Frontiers in Medicine)
ObjectivesThis study aims to systematically evaluate the efficacy of acupuncture on stroke-associated pneumonia (SAP).MethodsEnglish and Chinese databases were searched from their inception until 15 March 2024 to collect randomized controlled trials (RCTs). The risk of bias was assessed using Cochrane collaboration tools. RevMan 5.4.0 software was used to analyze the included studies, and the Grades of Recommendations, Assessment, Development, and Evaluation (GRADE) assessment was used to evaluate the quality of the study outcomes.Results16 studies involving 1,125 patients were included in this meta-analysis. Compared with the control group, the results showed that acupuncture significantly improved the effective rate [RR = 1.20, 95% CI (1.13, 1.27), P < 0.00001] and reduced the level of white blood cells (WBC) [MD = −6.52, 95% CI (−8.31, −4.73), P < 0.00001], C reactive protein (CRP) [MD = −6.50, 95% CI (−9.97, −3.03), P = 0.0002], neutrophil percentage (Neu%) [MD = −6.66, 95% CI (−8.96, −4.36), P < 0.00001], and procalcitonin (PCT) [MD = −0.81, 95% CI (−1.21, −0.40), P < 0.0001]. Additionally, acupuncture therapy shortened the duration of coughing [MD = −3.22, 95% CI (−4.73, −1.72), P < 0.0001], duration until disappearance of rales [MD = −3.99, 95% CI (−6.44, −1.54), P = 0.001], and duration of antibiotic use [MD = −4.51, 95% CI (−5.46, −3.57), P < 0.00001]. It also reduced the clinical pulmonary infection score (CPIS) [MD = −1.71, 95% CI (−2.71, −0.71), P = 0.0008] and National Institute of Health Stroke Scale (NIHSS) [MD = −3.93, 95% CI (−5.78, −2.09), P < 0.00001]. Moreover, acupuncture therapy increased the forced vital capacity (FVC) [MD = 0.46, 95% CI (0.02, 0.89), P = 0.04] and Forced Expiratory Volume in One Second (FEV1) [MD = 0.49, 95% CI (0.14, 0.84), P = 0.006].ConclusionThis study found that acupuncture has a positive effect in treating SAP. However, owing to the low-quality evidence, more rigorous studies are needed in the coming years to confirm these findings.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023462846, identifier CRD42023462846.